Measuring Spin⋅⋅⋅Spin Interactions between Heterospins in a Hybrid [2]Rotaxane. (9th March 2017) - Boulon, Marie‐Emmanuelle; Fernandez, Antonio; Moreno Pineda, Eufemio; Chilton, Nicholas F.; Timco, Grigore; Fielding, Alistair J.; Winpenny, Richard E. P.
Abstract: Use of molecular electron spins as qubits for quantum computing will depend on the ability to produce molecules with weak but measurable interactions between the qubits. Here we demonstrate use of pulsed EPR spectroscopy to measure the interaction between two inequivalent spins in a hybrid rotaxane molecule.